Jane Austen and C. S. Lewis: from Literature to Cinema. Analysis of Transposition - Sarapura Sarapura, Mercedes (2016)
The following is a proposal of an analysis of the transposition of literature to film of the novel Pride and Prejudice by Jane Austen and the essay A Grief Observed by C. S. Lewis. The first aim in both cases is to delve into the new contributions of the latest film version of Austin’s novel and the qualities and characteristics of the film version of the C. S. Lewis note pad, based on the theoretical contributions of such authors as Gerard Genette, Geoffrey Wagner, Brian Mcfarlane, among others. The second purpose is geared to the recognition of the exchange between film and literary language as a representative process of today society. The fact that the adaptations, historically seen with great skepticism, are now continually made and welcomed by the public, calls for a review and deepening of the studies made on that matter in order to know the current situation of the relationship between film and literature, its creative possibilities, audience expectations, prejudices and misgivings of experts, etc.